Penerapan Model Problem Based Learning untuk Meningkatkan Hasil Belajar Matematika Siswa pada Materi Teorema Pythagoras - Susanti Susanti; Hasmawati Hasmawati; Ariana Ariana (MUARA PENDIDIKAN : Jurnal Ilmiah Ilmu Pendidikan & Sosial Humaniora, 2026)
This study aims to determine the effect of the application of the Problem Based Learning (PBL) learning model on improving students' mathematics learning outcomes on the Pythagorean Theorem. The type of research used is a quasi-experimental design with a one-group pretest-posttest design. The subjects were 13 students of class VIIIA UPT SMPN 4 Mangarabombang who were selected through cluster random sampling techniques. The research instrument was a multiple-choice test of 10 questions that measured the understanding of the Pythagorean Theorem concept. Data analysis was carried out through the Kolmogorov-Smirnov normality test, the Paired Sample t-Test, and the N-Gain test. The results showed that the average student score increased from 30.77 in the pretest to 63.85 in the posttest, with a significance value of 0.000 (<0.05) indicating a significant difference between the pretest and posttest results. In addition, the N-Gain value of 0.49 is included in the moderate category, which means that the application of the PBL model has a positive effect on improving student learning outcomes on the Pythagorean Theorem